(untitled) (Politeja, 2020)
The Role of Language in Releasing from Inherited Traumas. Negotiations of the Social Position of the Silesian Minority in Serbian Banat The aim of the paper is to show the dependence between language, collective memory (also post-memory) and sense of identity. This issue is analysed using the example of an ethnic minority living in the village of Ostojićevo (Banat, Serbia) called ‘Toutowie.’ Their ancestors came in the 19th century from Wisła (Silesian Cieszyn, Poland); they left their homes because of great hunger and were looking for jobs in Banat. Narratives about the past contain traumatic experiences of the past generations transmitted in the Silesian dialect and constituting communicative memory. At the same time, a new Polish national identity is being constructed, supported by institutions and authorities; it carries a new image of the world and creates a new cultural memory. This new identity – shaped on the basis of national categories – leads to changes of its self-identification and gives the opportunity to raise its social position in the multi-ethnic Banat community.